Energy calibration of a BC501A liquid scintillator using a γ-γ coincidence technique - 言杰 刘荣 李澄 蒋励 鹿心鑫 朱通华 (Chinese physics C, 2010)
An accurate energy calibration of a BC501A liquid scintillator by means of Compton scattering of γ-rays is described.The energy resolution and the position of the Compton edge have been precisely determined using a γ-γ coincidence technique and fitting the coincidence spectrum with a Gaussian function superimposed on a quadratic polynomial for the background.The position of the Compton edge relative to the position of the maximum and the half height of the distribution in dependence on the relevant energy resolution is discussed in detail.The results indicate that the maximum energy of the recoil Compton electron does not occur at the half height distribution but at 0.90±0.05 of the maximum height in the energy range considered.The energy resolution varies from 15.6% to 8.02% for electrons in the energy region from 0.5 MeV to 3 MeV.